Effects of digital health counseling and behavioral interventions on weight management during pregnancy and postpartum: A systematic review and meta-analysis of randomized controlled trials - Sahar Khademioore; Alexandra M. Palumbo; Ahmad Sofi-Mahmudi; Taylor Incze; Kiara Pannozzo; Nicolette Christodoulakis; Rohan D’Souza; Gian Paolo Morgano; Nancy Santesso; Laura N. Anderson (PLoS ONE, 2025)
Objectives This systematic review aimed to evaluate the effects of digital health counseling or behavioral weight management interventions for preventing excessive gestational weight gain (GWG) among pregnant individuals of all body mass index (BMI) categories, compared to routine care. Methods We searched MEDLINE, Embase, CINAHL, ProQuest Dissertations/Theses, PsycINFO, and the Cochrane Central Register of Controlled Trials, up to February 2024. We included randomized controlled trials (RCTs) wherein pregnant women received counseling or behavioral interventions through digital health compared to routine care. Pairs of reviewers independently screened titles and abstracts and extracted data from eligible RCTs. Data were pooled using inverse-variance random-effects meta-analyses. We applied the Cochrane Risk of Bias 2.0 tool and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach to assess the magnitude and certainty of the effects. Results We included 18 trials. Moderate certainty evidence showed 0.78 kg lower GWG in the weight management digital health intervention group, compared with routine care (95% CI: −1.40 to −0.16 kg). This reduction was higher in individuals with BMI ≥ 25 kg/m2. Digital health interventions likely reduce the risk of excessive GWG (RR = 0.80; 95% CI: 0.68 to 0.95) and may result in little to no difference in the rate of cesarean birth (CB) (RR = 1.09; 95% CI: 0.81 to 1.48). Low-certainty evidence suggested that digital health weight management interventions may reduce the risk of gestational diabetes mellitus (GDM) (RR = 0.80; 95% CI: 0.57 to 1.12), pre-eclampsia (RR = 0.82; 95% CI: 0.51 to 1.33), and preterm birth (RR = 0.83; 95% CI: 0.53 to 1.28). High-certainty evidence showed that digital health weight management interventions have little to no effect on birthweight (MD = 0.00; 95% CI: −0.08 to 0.08). Conclusions Digital health interventions are effective in reducing GWG and excessive GWG based on BMI. Additionally, evidence suggests that these interventions may lower the risk of GDM, pre-eclampsia, and preterm birth. However, their impact on birthweight, GWG across all BMI categories, and the risk of CB is trivial.